Oxidative stress in moss Bryum caespiticium (Bryaceae) under the influence of high temperature and light intensity in a technogenically transformed environment - O. L. Baik; N. Y. Kyyak; O. M. Humeniuk; V. V. Humeniuk (Regulatory Mechanisms in Biosystems, 2021)
Mosses are pioneer plants in post-technogenic areas. Therefore, the question of adaptive reactions of mosses from these habitats represents a scientific interest. The research is devoted to the study of adaptive changes in the metabolism of the dominant moss species Bryum caespiticium Hedw., collected in the devastated territories of the Novoyavorivsk State Mining and Chemical Enterprise (SMCE) “Sirka (Sulfur)” exposed to hyperthermia and insolation, which cause oxidative stress in plants. The influence of these stressors on the activity and thermal stability of antioxidant enzymes, hydrogen peroxide content, anion radical generation and accumulation of prooxidant components in moss shoots was studied. The activity and thermal stability of peroxidase and superoxide dismutase (SOD) were analysed forB. caespiticium moss from different locations of northern exposure at the sulfur mining dump No 1 in summer and autumn. We established the dependence of the activity of antioxidant enzymes of moss on the intensity of light and temperature on the experimental plots of the dump No 1. In summer, the highest activity and thermal stability rates of peroxidase and SOD were observed. Under the conditions of the experiment in shoots of В. caespiticium from the northern peak of the dump under the influence of 2 hours temperature action (+ 42 ºС) the most significant increase in peroxidase activity was found by 1.78 times and SOD by 1.89 times, as well as increase in its thermal stability by 1.35–1.42 times, respectively. The increase in peroxidase and SOD activity, as well as the increase in their thermal stability caused by hyperthermia were negated by pre-processing with a protein biosynthesis inhibitor cyclohexamide, which may indicate the participation of the protein-synthesizing system in this process. The effect of increasing the thermal stability of enzymes can be considered as a mechanism of adaptation of the protein-synthesizing system to the action of high temperatures. Increase in the activity and thermal stability of antioxidant enzymes is caused primarily by changes in the expression of stress protein genes, which control the synthesis of specific adaptogens and protectors. The obtained results indicate that the extreme conditions of the anthropogenically transformed environment contribute to the development of forms with the highest potential abilities. The mechanism of action of high temperatures is associated with the development of oxidative stress, which is manifested in the intensification of lipid peroxidation and the generation of superoxide anion radical. It was found that temperature stress and high insolation caused an increased generation of superoxide anion radical as the main inducers of protective reactions in the samples of B. caespiticium from the experimental transect of the sulfur mining heap. It is known that the synthesis of Н2О2 occurs under stress and is a signal to start a number of molecular, biochemical and physiological processes of cells, including adaptation of plants to extreme temperatures. It is shown that high temperatures initiate the generation of hydrogen peroxide. Increased reactive oxygen species (ROS) formation, including Н2О2, under the action of extreme temperatures, can cause the activation of signaling systems. Therefore, the increase in the content of Н2О2 as a signaling mediator is a component of the antioxidant protection system. It is determined that adaptive restructuring of the metabolism of the moss В. caespiticium is associated with the accumulation of signaling prooxidant components (diene and triene conjugates and dienketones). The increase in primary lipid peroxidation products, detected by us, under the action of hyperthermia may indicate the intensification of free radical oxidation under adverse climatic conditions in the area of the sulfur production dump, which leads to the intensification of lipid peroxidation processes. The accumulation of radical and molecular lipid peroxidation products are signals for the activation of protective systems, activators of gene expression and processes that lead to increased resistance of plants.